Quality of life in patients with HTLV-I associated myelopathy/tropical spastic paraparesis - José Vicente Pereira Martins; Abrahão Fontes Baptista; Abelardo de Queiroz Campos Araújo (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To assess the quality of life (QoL) of patients with HTLV-I-associate myelopathy/tropical spastic paraparesis (HAM/TSP) and to correlate it with specific aspects of the disease. METHODS: Fifty-seven HAM/TSP patients completed the SF-36 QoL questionnaire. They were also asked about common complaints related to the disease, and we looked for associations between QoL and these complaints. RESULTS: Patients with HAM/TSP showed a strong negative association to QoL. Pain was the condition which most affected their QoL. The practice of physical activity is associated with better QoL in five out of eight domains of the scale. CONCLUSION: HAM/TSP leads to a poor QoL, mostly influenced by pain. Physical activity may have a positive association to QoL of these patients.